IMPLEMENTASI MODEL QUEST BASED LEARNING BERBASIS VIRTUAL REALITY UNTUK MENINGKATKAN DEEP LEARNING DAN PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN IPAS KELAS VI SD. - Riri Komalasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of this model aims to address the suboptimal science and social studies (IPAS) learning within the social interaction learning model at SDN Rawa Badak Utara 23 through Quest- Based Learning (QBL) integrated with Virtual Reality to create deep learning experiences and strengthen the Pancasila Student Profile. The implementation of the social interaction learning model was carried out over three meetings using a deep learning cycle. Activities included 360° virtual explorations to four countries, analytical discussions, mini- debates, and the creation of a "Green Travel Route" project. Holistic assessment combined observation, portfolio, and reflection. The model's implementation successfully created an immersive and interactive learning environment. Students showed significant improvement in collaboration, analysis, and creativity skills, evident from the quality of discussions and final project presentations. Student reflection journals also indicated a deeper understanding of global diversity and environmental awareness. The QBL model with Virtual Reality proved effective in transforming IPAS learning into a more meaningful experience. Follow-up actions include adopting the model for other themes and enriching it with more varied digital platforms.